2021
DOI: 10.1093/dote/doab054
|View full text |Cite
|
Sign up to set email alerts
|

Long-term neurodevelopment in children born with esophageal atresia: a systematic review

Abstract: Summary Background Although the survival rate of esophageal atresia (EA) has increased to over 90%, the risk of functional long-term neurodevelopmental deficits is uncertain. Studies on long-term outcomes of children with EA show conflicting results. Therefore, we provide an overview of the current knowledge on the long-term neurodevelopmental outcome of children with EA. Methods We performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…The rates of ID may change with longer follow-up, as found in a recent systematic review and meta-analysis of long-term neurodevelopment in children born with EA. 39 Infants up to 12 months of age had cognitive function within the normal limits in most studies, whereas two of four studies in school-aged children (6–18 years) found impaired cognitive performance with lower IQ levels. 17 , 38 …”
Section: Discussionmentioning
confidence: 91%
“…The rates of ID may change with longer follow-up, as found in a recent systematic review and meta-analysis of long-term neurodevelopment in children born with EA. 39 Infants up to 12 months of age had cognitive function within the normal limits in most studies, whereas two of four studies in school-aged children (6–18 years) found impaired cognitive performance with lower IQ levels. 17 , 38 …”
Section: Discussionmentioning
confidence: 91%
“…In a recent systematic review [33], secondary scoliosis after thoracotomy repair in EA children is reported in 13% of cases; according to a meta-analysis by Drevin et al [34], musculoskeletal complications are less common with the thoracoscopic approach. Considering only adult patients, a study by Sistonen et al [35] reported a 13-fold risk of scoliosis compared to the general population, with rib fusions post-thoracotomy being the strongest predictive factor; however, spinal surgery was never needed. As further studies are needed to define technique-related differences in musculoskeletal outcomes, efforts must be put also in defining the orthopedic follow-up in adult EA patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that complex surgeries and long anesthesia may lead to neurodevelopmental delays in cognition, learning, and behavior [ 48 ]. Recently, long-term neurodevelopment impairment in children with EA have been found; especially in motor function and in cognitive performance [ 49 ].…”
Section: Discussionmentioning
confidence: 99%